A modeling approach to identify the effective forcing exerted by wind on a prealpine lake surrounded by a complex topography. Issue 5 (18th May 2017) - Valerio, G.; Cantelli, A.; Monti, P.; Leuzzi, G.
Abstract: The representation of spatial wind distribution is recognized as a serious difficulty when modeling the hydrodynamics of lakes surrounded by a complex topography. To address this issue, we propose to force a 3‐D lake model with the wind field simulated by a high‐resolution atmospheric model, considering as a case study a 61 km 2 prealpine lake surrounded by mountain ranges that reach 1800 m above the lake's surface, where a comprehensive data set was available in the stratified season. The improved distributed description of the wind stress over the lake surface led to a significant enhancement in the representation of the main basin‐scale internal wave motions, and hence provided a reference solution to test the use of simplified approaches. Moreover, the analysis of the power exerted by the computed wind field enabled us to identify measuring stations that provide suitable wind data to be applied uniformly on the lake surface in long‐term simulations. Accordingly, the proposed methodology can contribute to reducing the uncertainties associated with the definition of wind forcing for modeling purposes and can provide a rational criterion for installing representative measurement locations in prealpine lakes. Key Points: An high‐resolution atmospheric model allowed to correctly describe the wind field in a lake surrounded by a complex topography A 3‐D lake model forced by the numerical wind field provided a better reproduction of the internal waves than the one forced by field data The analysis of the numerical wind field enabled us to identify suitable measuring stations for long‐term simulations